Ploughshares and Swords India's Nuclear Program in the Global Cold War - Sarkar, Jayita (Cornell University Press, 2022)
India's nuclear program is often misunderstood as an inward-looking endeavor of secretive technocrats. In Ploughshares and Swords, Jayita Sarkar challenges this received wisdom, narrating a global story of India's nuclear program during its first forty years. The book foregrounds the program's civilian and military features by probing its close relationship with the space program. Through nuclear and space technologies, India's leaders served the technopolitical aims of economic modernity and the geopolitical goals of deterring adversaries. The politically savvy, transnationally connected scientists and engineers who steered the program obtained technologies, materials, and information through a variety of state and nonstate actors from Europe and North America, including both superpowers. They thus maneuvered around Cold War politics and the choke points of the nonproliferation regime. Hyperdiversification increased choices for the leaders of the nuclear program but reduced democratic accountability at home. The nuclear program became a consensus-enforcing device in the name of the nation. Ploughshares and Swords is a provocative new history with global implications. It shows how geopolitical and technopolitical visions influence decisions about the nation after decolonization. Thanks to generous funding from the Swiss National Science Foundation, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.